Regeneration and reusability of non-conventional low-cost adsorbents to remove dyes from wastewaters in multiple consecutive adsorption–desorption cycles: a review - El Messaoudi, Noureddine; El Khomri, Mohammed; El Mouden, Abdelaziz; Bouich, Amal; Jada, Amane; Lacherai, Abdellah; Iqbal, Hafiz M. N.; Mulla, Sikandar I.; Kumar, Vineet; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Springer Nature, 2022)
The global economy’s growths due to industrialization, accompanied by urbanization high rate, have led to severe anthropogenic pollution impacting both the environment and human health. Regarding particularly the aquatic systems’ chemical pollution, as resulting mainly from the release of liquid effluents containing dye molecules and organic pollutants, it is therefore necessary to use innovative processes for treating the polluted water. At first sight, adsorption seemed like an excellent process due to its simplicity and efficiency, but this technique simply moves the dye from an aqueous medium to the adsorbent surface, thus creating sludges which are new pollution forms. Hence, we need to treat this polluted adsorbent in order to recover the removed dye and to reuse once more the adsorbent for others dye removal adsorption cycles. This review focuses on regenerating low-cost adsorbents (LCAs), saturated with dyes, by using different desorbing agents and on exploring their potential to be reused. These low-cost materials have been classified into four classes based on their origin: agricultural solid wastes; industrial by-products and wastes; natural materials; and sea materials and biomasses. Different chemical agents such as acids, bases, salts, organic solvents, alcohols, and chelating reagents have been used as eluents to regenerate the dye-covered adsorbents. Therefore, in the present review citing 210 literature articles, it is demonstrated the excellent regeneration and high reusability of the LCAs suited for dye removal from environmental wastewater. In this review paper, we show that the agricultural solid wastes (39.56%) are the most regenerated and reused, in comparison to, sea materials and biomasses (22.31%), industrial by-products and wastes (18.71%), and natural materials (19.42%).
Keywords: Desorbing agent; Dyes; Low-cost adsorbents; Regeneration; Reusability; Wastewater treatment